2006
DOI: 10.1080/01926230600867727
|View full text |Cite
|
Sign up to set email alerts
|

Normal Structure, Function, and Histology of Lymph Nodes

Abstract: Lymph nodes are traditionally regarded as having three compartments, the cortex, paracortex and medulla. B and T cells home to separate areas within these compartments, interact with antigen presenting cells, and undergo clonal expansion. This paper provides structural and functional details about how the lymph node brings lymphocytes and antigen presenting cells together. The concept of the lymphoid lobule as the basic functional and anatomic unit of the lymph node is developed and utilized to provide a frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
263
1
28

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(311 citation statements)
references
References 64 publications
2
263
1
28
Order By: Relevance
“…The lymphoid lobule is the basic anatomical unit of the LN and was described in 1975 [39]. In each lobule, stromal cells provide functional spaces within which T and B cells transiently reside in different areas: superficial B cell follicles and the deeper paracortical T cell zone [40]. This was first shown by Parrot et al [41], who demonstrated that radiolabeled T and B cells injected into an animal migrated specifically back to their respective areas.…”
Section: The Stromal Networkmentioning
confidence: 91%
See 1 more Smart Citation
“…The lymphoid lobule is the basic anatomical unit of the LN and was described in 1975 [39]. In each lobule, stromal cells provide functional spaces within which T and B cells transiently reside in different areas: superficial B cell follicles and the deeper paracortical T cell zone [40]. This was first shown by Parrot et al [41], who demonstrated that radiolabeled T and B cells injected into an animal migrated specifically back to their respective areas.…”
Section: The Stromal Networkmentioning
confidence: 91%
“…A similar segregation of T and B cells occurs in the white pulp of the spleen. Upon activation, Ag-specific cells are retained in the draining LN and the organ provides a suitable environment for all the steps of the developing response, being able to accommodate, screen, and feed a huge influx of cells, while remodeling its architecture to generate new functional niches such as germinal centers (GC) [40].…”
Section: The Stromal Networkmentioning
confidence: 99%
“…As shown by MALDI-TOF mass spectrometry, the O-glycan NeuAc␣2-3Gal␤1-3GalNAc (sialyl-T Ag) is highly abundant on both iDC and mDC and correlates with a high siglec-1 binding. Macrophages and DC coexist in the spleen, tonsils, and lymph nodes (65)(66)(67). Interaction of siglec-1 with its ligand on DC may serve two purposes, either to enhance intercellular contact or to induce or modulate signaling on DC.…”
Section: Discussionmentioning
confidence: 99%
“…The reader is referred to published reviews for details of normal histologic features of immune system organs in the adult laboratory rat and for specific procedures used for histological detection of xenobiotic-associated changes: thymus (Elmore 2006e, 2012Pearse 2006aPearse , 2006b, spleen (Cesta 2006b;Elmore 2006dElmore , 2012Suttie 2006), lymph nodes (Elmore 2006c(Elmore , 2006f, 2012Willard-Mack 2006), MALT (Cesta 2006a;Elmore 2006aElmore , 2012, and bone marrow (Elmore 2006b(Elmore , 2012Travlos 2006). The reader is referred to published reviews for details of liver involvement in immune responses Picut 2005, 2012) as well as further information on immunobiology of MALT (Jung, Hugot, and Barreau 2010;Kuper et al 2013).…”
Section: Relationship Of Immune System Function and Morphologymentioning
confidence: 99%